Religious and Ecclesiastical Media in the Hungarian Electronic Media Ecosystem - András Radetzky (Khazanah Journal of Religion and Technology, 2023)
Many academic works examine religious media institutions and media content producers operating in European countries, including Hungary, but most of them do so in an isolated way, mostly focusing on a particular content producer. The present study aims to provide a comprehensive picture of the operation of religious content producers in Hungary in a broader context, which considers the overall media system from a legal and economic point of view. First, we give a short retrospective overview about the history of Hungarian church press. Afterwards we examine the current legal framework for audiovisual regulation in Hungary. The conclusions are based on data obtained using three different methodologies. We have analyzed the freely accessible records of the Hungarian media authority (NMHH) and legislation, conducted a total of 6 in-depth interviews and an analysis of the content produced by each media outlet. The results of our research showed that in Hungary there is a disconnect between the concepts of church and religious media and that churches have hardly any comprehensive strategy to exploit the potential of digitalization. It can be concluded that church-owned media with religious content cannot be included in the present legal and economic framework without problems. Finally, an important question is whether and how church media are adapting to the changed environment. Our case studies show that the picture is mixed in this respect, because there is a lack of a coherent strategy among the actors on how service providers can adapt as effectively as possible to the new technological consumption patterns.